2023
DOI: 10.3390/anatomia2030026
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Diagnosis and Imaging of Femoral Shaft Fractures

Kathleen H. Miao,
Julia H. Miao

Abstract: Femoral shaft fractures (FSFs) are common orthopedic injuries, often resulting from high-energy trauma such as motor vehicle collisions, low-energy trauma, osteoporosis, or pathological conditions. They account for a significant portion of long bone fractures. Radiologic imaging plays a pivotal role in the diagnosis of these fractures, providing crucial information about fracture characteristics, associated injuries, and successful treatment and management planning. This paper provides a comprehensive review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…CT scans are essential in acute trauma contexts due to their high‐resolution imaging capabilities, which enable them to provide detailed information on bone structures and fractures 22 . Magnesium (MRI) is a highly effective modality for evaluating ligament, tendon and muscle injuries due to its exceptional soft tissue contrast 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT scans are essential in acute trauma contexts due to their high‐resolution imaging capabilities, which enable them to provide detailed information on bone structures and fractures 22 . Magnesium (MRI) is a highly effective modality for evaluating ligament, tendon and muscle injuries due to its exceptional soft tissue contrast 23 .…”
Section: Discussionmentioning
confidence: 99%
“…CT scans are essential in acute trauma contexts due to their high‐resolution imaging capabilities, which enable them to provide detailed information on bone structures and fractures. 22 Magnesium (MRI) is a highly effective modality for evaluating ligament, tendon and muscle injuries due to its exceptional soft tissue contrast. 23 According to our research, MRI demonstrated superior performance in assessing complex musculoskeletal injuries compared to CT and FAST in terms of sensitivity, specificity, PPV, NPV and overall accuracy.…”
Section: Discussionmentioning
confidence: 99%